New electron spin resonance (ESR) ages from Geißenklösterle Cave: A chronological study of the Middle and early Upper Paleolithic layers. Issue 133 (August 2019) - Richard, Maïlys; Falguères, Christophe; Valladas, Hélène; Ghaleb, Bassam; Pons-Branchu, Edwige; Mercier, Norbert; Richter, Daniel; Conard, Nicholas J.
Abstract: Geißenklösterle Cave (Germany) is one of the most important Paleolithic sites in Europe, as it is characterized by human occupation during the Middle and early Upper Paleolithic. Aurignacian layers prior to 37–38 ka cal BP feature both musical and figurative art objects that are linked to the early arrival in Europe of Homo sapiens . Middle Paleolithic layers yielded lithic artifacts attributed to Homo neanderthalensis . Since human occupation at the site is attributed to both Neanderthals and modern humans, chronology is essential to clarify the issues of Neanderthal disappearance, modern human expansion in Europe, and the origin of the Aurignacian in Western Europe. Electron spin resonance (ESR) dating was performed on fossil tooth enamel collected from the Middle Paleolithic layers, which are beyond the radiocarbon dating range, and from the nearly sterile 'transitional' geological horizon (GH) 17 and the lower Aurignacian deposits, to cross-check ESR ages with previous radiocarbon, thermoluminescence and ESR age results. The Middle Paleolithic layers were dated between 94 ± 10 ka (GH 21) and 55 ± 6 ka (GH 18) by ESR on tooth enamel. Mean ages for GH 17, at 46 ± 3 ka, and for the lower Aurignacian layers, at 37 ± 3 ka, are in agreement with previous dating results, thus supporting the reliability of ESR chronology for the base of the sequence where dating comparisons are not possible. These results suggest that Neanderthals occupied the site from Marine Isotope Stage (MIS) 5 to the second half of MIS 3 and confirm the antiquity of early Aurignacian deposits. The presence of an almost sterile layer that separates Middle and Upper Paleolithic occupations could be related to the abandonment of the site by Neanderthals, possibly during Heinrich Stadial 5 (ca. 49–47 ka), thus before the arrival of H. sapiens in the area around 42 ka cal BP. These dates for the Middle Paleolithic of the Swabian Jura represent an important contribution to the prehistory of the region, where nearly all of the excavations were conducted decades ago and prior to the development of reliable radiometric dating beyond the range of radiocarbon.